Genetic variants and anterior cruciate ligament rupture – Elastin proteins gene and fibromodulin gene polymorphisms - Ewelina Lulińska; Joanna Żelazny; Agnieszka Lulińska; Elżbieta Grzywacz; Aleksandra Stroińska-Pluta; Marek Sawczuk; Magdalena Stanulewicz (Baltic Journal of Health and Physical Activity, 2023)
Introduction: Anterior cruciate ligament (ACL) injuries are among the most common ligament injuries of the knee and often require reconstruction. The etiology of the molecular mechanisms of rupture of the anterior cruciate ligament (ACL) is poorly understood, and many external and internal factors have been associated with it, including genetics. This study aimed to investigate the association of sequence variants in the ELN and FMOD candidate genes with ACL ruptures based on the essential biological functions of these two proteoglycan-encoding genes in maintaining the structural integrity of tissues and regulating fibrillogenesis. Material and Methods: The partici-pants consisted of 229 (164 male and 65 female) individuals with a surgically diagnosed ACL rup-ture (ACLR) who qualified for ligament reconstruction and 192 (107 male and 85 female) healthy participants with no history of ACL injury (CON group). All 229 participants in the ACLR group sustained injuries through non-contact mechanisms. The chi-square tests were used for association analysis of ELN rs2071307 and FMOD rs7543148 between the anterior cruciate ligament rupture (ACLR) group and the control (CON) group. Results: It follows from the study that the tested group of athletes shows a statistically significantly more frequent AA genotype in the ELN rs2071307 gene polymorphism than the control group. However, looking at gender, one can observe that these are significantly more frequent. In the polymorphism of the FMOD rs7543148 gene, a significantly rarer TT genotype was observed in the study group compared to the control group and, similarly to the previous polymorphism, the TT genotype was significantly less frequent in the group of males com-pared to the control group. Conclusions: Genetic research in sports, especially concerning injuries connected to characteristic polymorphic variants of selected genes, is justified, particularly as regards gender-homogenous groups.